Flow Cytometric Analysis of Ploidy in Immunohistochemically Confirmed Examples of Malignant Epithelial Mesothelioma. Issue 3 (2nd January 2016) - Frierson, Henry F.; Mills, Stacey E.; Legier, Jacques F.
Abstract : Flow cytometry was used to compare the DNA content of 28 fresh effusion specimens that contained abundant proliferating mesothelial cells, with the ploidy profiles for 19 formalin-fixed, paraffin-embedded examples of malignant epithelial mesothelioma. Each mesothelioma lacked staining with periodic acid-Schiff (PAS) after diastase pretreatment. Nineteen of 19 mesotheliomas were immunoreactive for cytokeratin, 13 of 19 for epithelial membrane antigen, 0 of 19 for Leu-M1, and 0 of 19 for carcinoembryonic antigen. Each benign fluid specimen was DNA diploid. Nine of the deparaffinized mesotheliomas were DNA diploid, and seven had additional G0G1 peaks signifying DNA aneuploidy. Histograms from the remaining three mesotheliomas showed G0G1 peaks with prominent shoulders, probably indicating low-degree hyperdiploidy. The results suggest that ploidy analysis by flow cytometry might be useful for the separation of mesothelioma from proliferating mesothelial cells in effusion specimens. Although only 53% of the mesotheliomas were DNA aneuploid, the finding of DNA aneuploidy in an effusion specimen that contains atypical mesothelial cells would strongly support a diagnosis of mesothelioma.